Utilizing Post Quantity, Views and Reviews to Increase User Generated Content and Create Interest in Purchasing Cosmetic Products - Naomi Theresia Setiawan; Gede Sri Darma (Publikasi Indonesia, 2025)
The purpose of this study is to explain the effect of post quantity, view and review on the credibility of the source and the usefulness of information from UGC, then explain the effect of UGC source credibility on consumer attitudes and the usefulness of information from UGC, then explain the effect of the usefulness of information from UGC on consumer attitudes and explain the effect of consumer attitudes on User Generated Content (UGC) on interest in buying cosmetic products. The design of this study is associative research. This research was conducted in Denpasar City. The population of this study were all female consumers in all areas of Denpasar City who had watched cosmetic video reviews on the TikTok and YouTube social media platforms. The sampling technique used in this study was purposive sampling. The number of samples studied was 115 respondents. The analysis techniques used were descriptive statistical analysis and Partial Least Square (PLS) Analysis. The results of the analysis showed that the quantity of posts, views and reviews had a significant positive effect on the credibility of sources and the usefulness of information from UGC, then the credibility of UGC sources had a significant positive effect on consumer attitudes and the usefulness of information from UGC, then the usefulness of information from UGC had a significant positive effect on consumer attitudes and consumer attitudes on User Generated Content (UGC) had a significant positive effect on interest in buying cosmetic products.